Shared authorship : Sonesnat, audiovisual production workshop - Serra Navarro, David; Vallès Villanueva, Joan; Vayreda Puigvert, Marian (Pulso. Revista de educación, 2012)
The following paper shows the development of an educational experience based on participatory learning, understanding relational processes in a artistic scene. Using the methodology applied in the artistic work Sonesnat, we propose a creative workshop that encourages a trialogue: the artwork as a process, the collective experience as an engine to produce meanings, and the shared authorship through immaterial products.
Keywords: Co-authoring; Inquiry; Sonesnat; Audiovisual; Relational Process; Arts Education